Use of novel oral anticoagulant agents in venous thromboembolism - Madan, Shivanshu; Shah, Shenil; Dale, Patrick; Partovi, Sasan; Parikh, Sahil A. (Cardiovascular Diagnosis and Therapy; Vol 6, No 6 (December 29, 2016): Cardiovascular Diagnosis and Therapy (Advanced Venous Imaging and Image-guided Venous Interventions), 2016)
New oral anticoagulants (NOAC) serve as alternatives for patients currently using warfarin for the prevention and treatment of venous thromboembolic (VTE) disease. This article provides a brief summary of the clinical use of these drugs as well as a review of the landmark clinical trials which evaluated described their safety and efficacy. As more data becomes available, a fundamental understanding of these medications will be vital to cardiovascular practitioners managing patients with VTE.